A qualitative exploratory study of UK first-time fathers’ experiences, mental health and wellbeing needs during their transition to fatherhood - Jane Sandall; Sharin Baldwin; Mary Malone; Debra Bick (BMJ Open)
Objectives To develop an understanding of men’s experiences of first-time fatherhood, their mental health and wellbeing needs.Design A qualitative study using semi-structured interviews. Data were analysed using framework analysis.Setting Two large National Health Service integrated care trusts covering four London (UK) local authority boroughs.Participants First-time fathers with children under 12 months of age were included. Maximum variation sampling was used, with 21 fathers recruited. Ten of these men described their ethnic background as Indian, seven as White British, one as Spanish, one as Black African, one as Black Caribbean and one as Pakistani. Participants’ ages ranged from 20 to over 60 years; completion of full-time education ranged from high school certificate to doctorate level; and annual income ranged from £15 000 to over £61 000. Non-English speaking fathers, those experiencing bereavement following neonatal death, stillbirth, pregnancy loss, sudden infant death, and fathers with existing severe mental illnesses were excluded.Results Nine major categories were identified: ‘preparation for fatherhood’, ‘rollercoaster of feelings’, ‘new identity’, ‘challenges and impact’, ‘changed relationship: we’re in a different place’, ‘coping and support’, ‘health professionals and services: experience, provision and support’, ‘barriers to accessing support’, and ‘men’s perceived needs: what fathers want’. Resident (residing with their partner and baby) and non-resident fathers in this study highlighted broadly similar needs, as did fathers for whom English was their first language and those for whom it was not. A key finding of this study relates to men’s own perceived needs and how they would like to be supported during the perinatal period, contributing to the current evidence.Conclusions This study provides insight into first-time fathers’ experiences during their transition to fatherhood, with important implications for healthcare policy makers, service providers and professionals for how perinatal and early years services are planned and provided for both new parents.